The Effect of Parents’ Interpersonal Communication and Students’ Empathy on Prosocial Behaviors of Buddhist Students - Novianti Novianti (Universitas Veteran Bangun Nusantara, 2022)
This study aims to investigate the effect of parents’ interpersonal communication and students’ empathy on the prosocial behaviors of Buddhist students. This study employed a quantitative method to reveal whether there is an effect of parents’ interpersonal communication and students’ empathy on the prosocial behaviors of Buddhist students. The instrument used to collect data was questionnaire. The results indicated that there was a significant effect of parents’ interpersonal communication on the prosocial behaviors of Buddhist students with significance level 0.046 and t-value 2.124. Good parents’ interpersonal communication improved prosocial behaviors of Buddhist students. Moreover, students’ empathy had a significant effect on students’ prosocial behavior with significance level 0.000 and t-value 15.021, which means that higher empathy will result in better prosocial behaviors. Based on the regression analysis, parents’ interpersonal communication and students’ empathy affected the prosocial behavior of Buddhist students at junior high schools in Wonogiri as much as 92.9%. The implication of this study is parents should build a good interpersonal communication with their children and develop their empathy so that children can positively respond to parents’ guidance which will lead to better prosocial behavior.